Is the European Community an Optimal Currency Area? Optimal Taxation Versus the Cost of Multiple Currencies - Canzoneri, Matthew B.; Rogers, Carol Ann (American Economic Review, 1990)
We propose a view of optimal currency areas that is based on the principles of public finance. Inflation taxes are distortionary, and an optimal spreading of tax distortions may require high inflation in one region and low inflation in another. Each region would need its own currency to do this. On the other hand, multiple currencies imply valuation and currency conversion costs, which impede trade between regions. This tradeoff is explored in the context of the European Community's debate over a common currency, using a two-country variant of Lucas and Stokey's cash-in-advance model.